The Role of Character Education and Religious Values in Prevention of Sexual Violence - Nurcahyawati, Enny; Ramliyana, Randi; Ramdhan, Vickry; Radita, Hana Cintia Ayu; Puspitasari, Anggun Citra Dini Dwi; rosida, Ida (Advances In Social Humanities Research, 2024)
Discussion on national character has been included in the legal regulation, that every Indonesian society is expected to be an individual who understands morals and is accustomed to doing good things in life. Developments in the era of globalization are increasingly massive, ultimately having an impact on the elimination of national character. In the end, several problems arise due to the shift in national character, one of which is the occurrence of free association which has an impact on sexual harassment. This study uses a library research method by utilizing secondary data as reference material. In an effort to prevent sexual harassment, character education and the application of religious values for an individual are very important. Because these two things can ultimately lead an individual to maintain association; manners; politeness; and norms taught in religious values.